ANALISIS REDUPLIKASI KATA KERJA DALAM KALIMAT BAHASA MANDARIN - Niza Ayuningtias (GENTA BAHTERA: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
Morphology is part of linguistic study about morpheme and analysing structure and classification of words.There are two kinds of morphemes. They are free morpheme and bound morpheme. Free morpheme is amorpheme that can stand alone as a word. While bound morpheme is a morpheme that cannot stand alone as aword or needs other morphemes. The process discussing about words in morphology is called morphemicprocess or morphology process. Reduplication is a kind of morphemic process. There are one reduplications(reduplication of verb) discussed in this research. The purpose of this research is to describe patterns ofmorphemic reduplication in Mandarin sentences. The theory used in this research is structural morphologytheory from Ramlan an instrument to analyze the data. Structural morphology is a kind of linguistics discussabout the structure and the process of word formation. The method used in this research is qualitative researchmethod which describes about structures and patterns of morphemic reduplication in Mandarin. Based on theresults of the analysis can be seen that the reduplication of verbs there is repetition of the whole and there is alsoa repetition in combination with affix. The pattern of verb reduplication is the repetition of the monosilabelverb has AA pattern, the repetition of infected verbs has A N A pattern and the repetition of the verbs dislabikhas an ABAB pattern AbstrakMorfologi adalah bagian linguistik yang mempelajari morfem serta menganalisis struktur, bentuk,dan klasifikasi kata-kata. Ada dua jenis morfem, yaitu morfem bebas dan morfem terikat. Morfembebas secara morfemis adalah morfem yang dapat berdiri sendiri, sedangkan morfem terikat adalahmorfem yang tidak bisa berdiri sendiri dan membutuhkan morfem lainnya. Proses morfemis salahsatu di antaranya adalah proses reduplikasi. Reduplikasi yang dibahas dalam penelitian ini adalahreduplikasi kata kerja. Tujuan dari penelitian ini adalah untuk mendeskripsikan jenis-jenis danpola-pola reduplikasi morfemis dalam kalimat bahasa Mandarin. Teori yang digunakan dalampenelitian adalah teori morfologi struktural oleh Ramlan sebagai alat untuk menganalisis datayang ada. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif yangbersifat deskriptif dengan memaparkan jenis-jenis dan pola-pola reduplikasi morfemis bahasaMandarin. Berdasarkan hasil analisis dapat diketahui bahwa pada reduplikasi kata kerja terdapatpengulangan seluruh dan ada juga yang mengalami pengulangan yang berkombinasi denganafiks. Pola reduplikasi kata kerja yaitu pengulangan kata kerja monosilabel memiliki pola AA,pengulangan kata kerja berinfiks memiliki pola ANA dan pengulangan kata kerja dislabik memilikipola ABABKata kunci : morfologi, morfem, reduplikasi kata kerja